Comparative study on the infection rates of different Glossina species for East and West African Trypanosoma vivax stocks - Moloo, S.K.; Kutuza, S.B.; Desai, J. (Cambridge University Press, 1987)
Teneral maleOlossina morsitans centralis, G. austeni, G. palpalis palpalis, G. p. gambiensis, G. fuscipes fuscipes, G. tachinoidesandG. brevipalpiswere fed on the flanks of Boran calves infected withTrypanosoma vivaxstock ILRAD 2241 isolated from a cow in Likoni, Kenya; stock ILRAD 2337 isolated from a cow in Galana, Kenya; stock ILRAD 1392 isolated from a cow in Nigeria; or, stock EATRO 1721 isolated fromG. m. submorsitansin Nigeria. The tsetse were fed on the infected hosts for 24 days and were then dissected to determine the infection rates. InG. m. centralisandG. brevipalpis, the mature infection rates ofT. vivaxfrom Kenya were 61·1 %, and 75·3% for ILRAD 2241, and 36·2% and 58·2% for ILRAD 2337, respectively. InG. austeniand in the fourpalpalisgroup of tsetse, the rates for these two stocks were very low and ranged from 0% inG. p. palpalisto 1·8% inG. austenifor ILRAD 2241 and from 0% inG. f. fuscipesto 5% inG. tachinoidesfor ILRAD 2337. In contrast, the hypopharyngeal infection rates ofT. vivaxfrom Nigeria were quite high in all the 7 tsetse species and sub-species. They ranged from 55·5% inG. austenito 919% inG. p. gambiensisfor ILRAD 1392, and from 71·4% inG. austeneito 97·1 % inG. brevipalpisfor EATRO 1721. It is suggested that successful establishment ofT. vivaxinfection in a particular tsetse species could depend on the biochemical characteristics of its attachment sites in the food canal and the efficiency of bloodstream trypomastigotes of a particularT. vivaxstock to attach to such sites and undergo complete development to meta-trypanosomes in the hypopharynx of the vector.